RESILIENCE OF COLONIAL ARCHITECTURAL ELEMENTS IN THE LAWANG SEWU BUILDING - Izzata , Abdurrobbi; Ardiyanto, Fernanda Dwi; Shanzani, Haris Alizzar; Fauzan, Muhammad Allam; Ahmad, Rafif Aydin; Harmunisa, Yusvika Ratri (ADBE, 2025)
Lawang Sewu is a historical building located in the city of Semarang, Central Java, Indonesia. The existence of this building is inseparable from the historical development of Semarang City. During the Dutch colonial period, the building was used as the office of a railway company. These buildings were connected by a long corridor called the "thousand doors." The architectural style of Lawang Sewu uses Colonial Architecture characterized by the use of gables on the building’s facade and curved ornaments. Architectural resilience refers to the ability of architectural elements to withstand and adapt to changes in the environment, both physically, socially, and economically. This study aims to analyze the resilience of Lawang Sewu in maintaining its architectural style in the modern era. The research method used is qualitative literature study by collecting literature data from various sources about Lawang Sewu building. In the midst of this situation, Lawang Sewu, a historical building in Semarang, Central Java, emerges as an important example in the effort to build cultural resilience.